Integrated application of OEE with quality tools to a fleet of industrial waste handling equipment - Sancheta, Larissa do Nascimento; Feroni, Rita de Cassia (Brazilian Journal of Production Engineering, 2021)
The concept of Overall Equipment Effectiveness (OEE) is commonly used in industrial processes to identify and mitigate wastes. The application of this indicator in the management of industrial solid waste is still scarce and deserves to be explored. This paper aims to apply the OEE for the analysis of the efficiency of waste handling equipment in a pulp and paper industry, in addition to identifying and analyzing the main losses that reduce the efficiency of equipment. The research was conducted with two trucks, one of biomass and one of unpicked wood, whose OEE’s were 62% and 71%, respectively. After analyzing the main losses through the use of quality tools, and implementing improvement actions, it was possible to increase the bucket occupancy rate by 12%. The work concluded that the company must expand the application of OEE to the entire fleet of equipment in order to constantly act on the waste of the process.
Keywords: OEE; industrial waste; quality tools; TPM